Technical Solution for Scutching the Raw Bast Material - Berezovsky, Yu.V. (Science and Innovation, 2024)
Introduction. The research deals with problems of development of scientific framework for resource-saving technologies for complex processing of bast crops. Problem Statement. In recent years, the problem of sustainable development of the country has aggravated. The critical features of production flowchart for processing bast raw material in Ukraine in order to develop adequate scenarios of its development have been identified. Purpose. The purpose of the research is to develop theoretical aspects of obtaining bast fibers with given qualitative indicators. Materials and Methods. The research uses the methods of theoretical generalization and comparison, analysis and synthesis. The search of ways for improving the quality and expanding the assortment of high-quality bast products using different methods of treatment has been discussed. Results. The modern level of domestic and foreign research works on the problems and promising directions of development of primary processing of bast fibers has been generalized. The theoretical aspects of more efficient use of raw flax materials available in the country have been elaborated. Conclusions. Based on the research of anatomical and chemical structure of bast stems and configurations of a group of breaking-and-shaking and scutching-and-cleaning machines for pretreatment of industrial fiber, the need of creating a new device for mechanical treatment of these crops to produce fiber with given quality has been theoretically substantiated and experimentally proved. New ways for stem destruction based on the compression, fracture, sliding flexure, scraping, inertial forces, friction, pressure, and tension, which contribute to the stem disintegration and increase in fibers separation, have been proposed. These ways are based on the device for separating the woody parts and deflaking. Innovational configuration of scutching unit for processing bast raw materials, which provides raising efficiency of breaking the connections between woody part and fiber of bast raw material and separating the fibers from woody part and other non-fibrous impurities have been developed. This scutching unit has universal application for processing the stems of bast crops.